Corporate Governance in Islamic Financial Institutions: Challenges and Opportunities - Ruki Ambar Arum; Abdul Azis; Afrianto; Hasrul Wijaya; Andi Aswani (Universitas Muhammadiyah Makassar, 2025)
This study investigates the challenges and opportunities of corporate governance in Islamic Financial Institutions (IFIs) by employing a Systematic Literature Review (SLR) approach. Corporate governance in IFIs is distinct from conventional institutions due to the dual requirement of complying with international governance standards and Shariah principles. The review synthesizes findings from peer-reviewed articles published between 2019 and 2024 to provide a comprehensive understanding of the governance landscape in IFIs. The results highlight several persistent challenges, including the lack of standardization in Shariah Supervisory Board (SSB) practices, regulatory fragmentation across jurisdictions, and limited expertise among governance professionals. These challenges create inconsistencies in the effectiveness of Shariah governance and may undermine institutional credibility. However, the study also identifies considerable opportunities. Strengthening corporate governance enhances stakeholder trust, increases investor confidence, and positions IFIs as leaders in ethical and sustainable finance. Furthermore, the adoption of digital governance tools, such as blockchain and artificial intelligence, offers innovative solutions to improve transparency, accountability, and compliance monitoring. This study contributes to the literature by consolidating recent insights and proposing recommendations for harmonization, capacity building, and sustainability integration. It concludes that robust governance frameworks are critical for the long-term stability of IFIs and their role in advancing ethical finance aligned with the United Nations Sustainable Development Goals (SDGs).